Strategies for Developing Lexical Competence in the Context of Teaching English in Higher Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, the author examines the issue of a communicative approach to teaching vocabulary, subordinated to mastering other aspects of language - grammar and phonetics, which is intertwined with them, but is especially activated when working on a text, in conversational practice classes, while developing reading skills and listening comprehension. Effective explanation of new words with the help of visual aids - real objects, drawings, pictures, tables, photographs, etc. In which, it is convenient to semanticist the meaning of most words - realities that are easily represented in a "visual way", using examples of terms; room, bed, bed, pillow, mattress, pillowcase, blanket, bedspread and others.